E-learning in secondary Schools in Kenya: A Case of the NEPAD E-schools - Ayere, Mildred; Odera, F; Agak, John (Educational Research and Reviews, 2010)
The New Partnership for Africa's Development (NEPAD) schools were set up as centres of excellence in Information and Communication Technology (ICT) integration, so that other schools could copy their model in e-learning. It was for this reason that they were provided with computers, e-materials, internet appliances and trained personnel. But to gauge their levels of success as e-learning centres there was need to compare them to other schools offering ICT education in Kenya. It was for this reason that this study compared the application of the e-learning in NEPAD and non-NEPAD schools in Kenya. Specifically, the study: Identified significant differences in levels of integration of ICT in curriculum subjects; surveyed the differences in use of e-materials in education research; examined availability of e-libraries; identified significant differences in academic performance of NEPAD and non-NEPAD schools attributed to e-learning. The study used a combination of an exploratory approach using descriptive survey and ex-post-facto design. It was carried out in six of the eight provinces in Kenya, where the NEPAD schools are located. It targeted 1600 form four students from 35 secondary schools involved in ICT education (NEPAD schools included). Saturated sampling was used for the six NEPAD schools while six non-NEPAD schools were selected through simple random sampling. The sample consisted of three officials from the ministry of education, twelve principals and twelve heads of ICT department (HODs), and 570 of the form four students. The main data collection instrument was the questionnaire; administered to the students, the principals, and the HODs. The interview schedule was administered to the ministry of education personnel while an observation checklist was used as a confirmatory tool. Analysis was done using both descriptive and inferential statistics. The study found that, there was a significant difference in the application of e-learning in NEPAD and non-NEPAD schools. Based on these findings, it was recommended that schools involved in ICT education should intensify teacher facilitation and support teacher roles that are required in e-learning Key words: E-Learning, ICT integration, ICT education, new partnership for Africa's development (NEPAD).
Keywords: ⛔ No DOI found

Accessibility and Utilization of ICTs Among Secondary School Teachers in Kenya - Kiptalam, GK; Rodrigues, AJ (2010)
Keywords: ⛔ No DOI found

246 6 Accessibility and Utilization of ICTs Among Secondary School Teachers in Kenya - University, G. (2010)
This paper looks at levels of access and extent of use of Information and Communication Technologies (ICTs) among teachers in selected Kenyan secondary schools. For the past few years, an assortment of ICTs such as computers, lap tops, projectors, printers, e-blackboards and mobile phones have been available to teachers for use in integration of teaching and learning in schools. The paper attempts to establish how many teachers have access to the schools’ computers, their ICT literacy skills level and the level of ICT integration in subjects taught. The findings show that the use of ICT and its integration in the teaching and learning in secondary education is getting more widespread; and increasingly used among teachers as a means of communication and for information searching. Access rates for teachers have been observed to be much higher in educational institutions that have made effective ICT investments in education, translating into better utilization of ICT related technologies. Strategies have been suggested on how to utilize ICT to improve educational outcomes and recommendations given, on issues that touch on ICT access and infrastructure; human resources and training, policy environment, financing and ICT investment, curriculum development and locally relevant content.

Use of low cost wireless communication technology for education in rural Kenya | Proceedings of the 4th ACM Workshop on Networked Systems for Developing Regions - Mayeku, B.; Kilwake, J.; Bertarelli, F (2010)